Pengaruh Implementasi Pajak, Budaya, Teknologi Melalui Inovasi Terhadap Kinerja Perusahaan - Suhendra, Suhendra (AKUNTOTEKNOLOGI : JURNAL ILMIAH AKUNTANSI DAN TEKNOLOGI, 2023)
This study aims to analyze the effect of tax policy, company culture, technology through innovation to company financial performance. This study uses primary data from 70 responden. The analysis data use structural equation modeling with SmartPLS 3.2.8. The results show that tax policy and technology have positive effect on company financial performance and the company culture has no effect on company financial performance. Tax policy and technology have positive effect on company financial performance, with this condition company need to focus on how to maximizing the technology and improve the capability of tax team in company and get benefit to increase the company performance. And the company culture has not directly impact to company financial performance, but with the innovation as an intervening company culture can make the positive effect to company financial performance. Company need to socialize company culture with different method. For the future research can develop to how the tax policy can effect to the innovation of company